Doença renal crônica em pacientes pediátricos: avaliação de mediadores imunes e índices derivados do hemograma. - Aislander Junio da Silva (2021)
Chronic kidney disease (CKD) is characterized by progressive loss of function leading to kidney failure. CKD is less common in children than in adults. In childhood, the main causes include congenital abnormalities of the kidneys and urinary tract (CAKUT), followed by glomerulopathies, in addition to cystic diseases and tubulopathies. There are factors that favor the advancement of CKD such as; oxidative stress, endothelial dysfunction and inflammation. The latter promotes tissue injuries that make homeostasis of the renal parenchyma impossible, feeding back the inflammatory process that consequently aggravates the CKD. The present study aimed to evaluate inflammatory markers such as Interleukin 17 (IL-17), Interleukin 33 (IL-33), Chemokine CXC 16 (CXCL16), Annexin A1 (AnxA1), Interleukin 4 (IL-4), Interleukin 10 (IL-10), Neutrophil-lymphocyte ratio (NLR), Neutrophil-lymphocyte-ratio-derived (dNLR) , Lymphocyte-monocyte ratio (LMR) and Systemic Inflammation Response Index (Siri) in pediatric patients with CKD, according to the different etiologies/stages. Eighty-five children were divided into seven groups and evaluated, namely; Group IA: children with CKD caused by glomerulopathies in stage 1 or 2; Group IB: children with CKD caused by glomerulopathies in stage 3 or 4; IIA: children with CKD caused by CAKUT in stage 1 or 2; IIB: children with CKD caused by CAKUT in stage 3 or 4; III: children with CKD caused by other etiologies in stage 3 or 4. In addition, a broader group was created, comprising all patients with CKD, including stages 1 to 4 (Group IV), and finally a control group (Group V), composed of healthy individuals with ages compatible with pediatric patients Serum concentrations of inflammatory markers were determined by the enzyme immunoassay technique and indices derived from the blood count were determined through calculations with blood count parameters obtained from the original project database. The results revealed a reduction in serum markers IL-17, IL-33 and CXCL16 in patients with CKD (including all stages of the disease) compared to control. AnxA1, IL-4 and IL-10 showed no differences between the two groups. LMR was reduced in patients with CKD compared to control, and Siri increased in patients with CKD compared to control. For the NLR and dNLR indices there were no differences between patients with CKD versus control. Pro-inflammatory mediators such as IL-17 and CXCL16 were showing promise in patients with CKD, as well as blood count-derived indices such as LMR and Siri reflected the pro-inflammatory state of the study patients.